WNT7A Promotes EGF-Induced Migration of Oral Squamous Cell Carcinoma Cells by Activating β-Catenin/MMP9-Mediated Signaling - Xie, Hui; Ma, Yadong; Li, Jun; Chen, Huixia; Xie, Yongfu; Chen, Minzhen; Zhao, Xuyang; Tang, Sijie; Zhao, Shuo; Zhang, Yujie; Du, Jun; Zhang, Feimin; et al. (Frontiers in Pharmacology, 2020)
Aims and hypothesis: Epidermal growth factor (EGF) has been shown to induce the migration of various cancer cells. However, the underlying signaling mechanisms for EGF-induced migration of oral squamous cell carcinoma (OSCC) remain to be elucidated. WNT7A, a member of the family of 19 Wnt secreted glycoproteins, is commonly associated with tumor development. It is mostly unknown whether and if so, how EGF modulates WNT7A in OSCC cells. The role of WNT7A in OSCC was thus investigated to explore the underlying signaling mechanisms for EGF-induced migration of OSCC. Methods: Cell migration was measured by Wound healing assay and Transwell assay. Western blotting was carried out to detect the expression of WNT7A, MMP9, β-catenin, p-AKT, and p-ERK. The cells were transfected with plasmids or siRNA to upregulate or downregulate the expression of WNT7A. The location of β-catenin was displayed by Immunofluorescence Microscopy. Immunohistochemistry was carried out to confirm the relation between WNT7A expression and OSCC progression. Results: The present study showed that the levels of WNT7A mRNA and protein were increased by EGF stimulation in OSCC cells. Besides, it was proved that p-AKT, but not p-ERK, mediated the expression of WNT7A protein induced by EGF. Furthermore, the inhibition of AKT activation prevented the EGF-induced increase of WNT7A and matrix metallopeptidase 9 (MMP9) expression and translocation of β-catenin from the cytoplasm to the nucleus. Moreover, histological analysis of OSCC specimens revealed an association between WNT7A expression and poor clinic prognosis of the disease. Conclusions: The data of this paper indicated that WNT7A could be a potential oncogene in OSCC and identified a novel PI3K/AKT/WNT7A/β-catenin/MMP9 signaling for EGF-induced migration of OSCC cells.